Produksi Bioetanol Dari Rumput Laut dan Limbah Agar Gracilaria sp. dengan Metode Sakarifikasi Yang Berbeda - Adini, Saniha; Kusdiyantini, Endang; Budiharjo, Anto (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The Indonesia needs of Bioethanol were 390.000 kL in 2012, but the local ethanol production only able to cover less than 4% from the needed. The high demand of the bioethanol encourage for another innovation in ethanol production more efficient and effectively. Seaweeds and the residual pulp of Gracilaria sp. could be useful as substrate for bioethanol production, because of the high amount of polysaccharide, cellulose and galactan type. Unfortunately, this cellulose and galactan had through the saccharification process first, before they can be used as substrates in bioethanol production. This study examined the difference between two saccharification process which are acid hydrolisis using H2SO4 1% and enzymatic process using Aspergillus niger on the use seaweed and the residual pulp of Gracilaria sp. for bioethanol production. Bioethanol production been conducted for 5 days and in each 24 hour, the sampling for cell number variable, reduction sugar amount variable, and medium fermentation pH variable had been retrieved. The ethanol amount calculation in the last incubation phase conducted using distillate fermentation spesific gravity methode. The highest ethanol was obtained 5,50% by treatment using seaweed medium with acid hydrolisis. The anova analysis result showed that interaction between medium variable and hydrolisis didn’t have signifficant influence toward ethanol product. It showed that seaweed and the residual pulp of Gracilaria sp. had same quality and they can be useful as main component of bioethanol production which are hydrolisis by enzymatic or acid hydrolisis. Key Words : Gracilaria sp., the residual pulp, saccharification, reducing sugar, ethanol